A transgene targeted to the zebrafish nkx2.4b locus drives specific green fluorescent protein expression and disrupts thyroid development. Issue 11 (5th August 2020) - Hutcheson, David A.; Xie, Yuanyuan; Figueroa, Priscilla; Dorsky, Richard I.
Abstract: Background: With the goal of labeling and manipulating the zebrafish hypothalamus, we sought to target a green fluorescent protein (gfp) transgene to the expression domains of nkx2.4b, a gene expressed during hypothalamic and thyroid development. We combined transcription activator‐like effector nucleases (TALENs)‐mediated mutagenesis with a targeting construct to enable insertion of a gfp transgene into the endogenous nkx2.4b genomic locus. Results: Injection of TALENs targeted to the first exon of nkx2.4b created a predicted null allele, and homozygous mutant embryos displayed loss of thyroid markers. From embryos injected with both TALENs and a targeting construct carrying a gfp transgene, we recovered a line in which GFP was expressed specifically in the hypothalamus and thyroid. Fish homozygous for this allele lacked exon 1 of nkx2.4b and exhibited hypothyroid phenotypes. Conclusions: By combining TALENs injections with a targeting construct that contained a gfp transgene, we were able to recover an allele in which GFP is expressed in the nkx2.4b expression domains, with homozygous phenotypes suggesting the creation of a loss‐of‐function transgenic line. These results demonstrate the creation of a useful tool for studying hypothalamus and thyroid development. Key Findings: Transgene targeting to the nkx2.4b locus in zebrafish. Disruption of the nkx2.4b gene by TALENs mutagenesis and transgene insertion both result in hypothyroid phenotypes. The inserted transgene expresses GFP in the hypothalamus and thyroid.